Assessment of urban heat island in Kathmandu valley (1999-2017) - Magar, Dipendra Salami; Magar, Ramesh Kumar Salami; Chidi, Chhabi Lal (Geographical Journal of Nepal, 2021)
Growing urbanization results built up surfaces converting from agriculture land, forest and other natural land cover surfaces. Increasing built up surfaces, means of transport and industrial activities are major results for increasing temperature in the city area as compared to other areas. Increasing heat is a concern to human health of the people living in urban areas. Increasing temperature in the city area in developing countries is being a growing concern. Kathmandu valley is one of the most rapidly growing urbanization in Nepal. The present study aims to assess the changing Land Surface Temperature (LST) in Kathmandu valley using LANDSAT 7 images. Similarly, Urban Heat Island (UHI) effect was evaluated in land use categories which were derived from Google Earth images. Study revealed that built up area contributed highly to increase land surface temperature. New built up with compact settlement area has higher land surface temperature as compare to other land use/land cover surfaces. City core has higher LST as compared to less urbanized and surrounding parts. The LST has highly increased during 1999 to 2017 with increasing urbanization. However, the ecological condition of UHI effect is not so bad till date but the study result indicated the continuous increasing urbanization may result worse ecological condition in Kathmandu Valley in the future.